MEMBANGUN BANGSA INDONESIA DENGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Andang Sunarto (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The rapid development of information and communication technology (read: ICT) has changed the procedure for humans act and behave today, as well as college graduates as an elite human capital, particularly in relation to the process of communication and interaction. It is a fact that almost all industrial fields and aspects of modern life do not escape the reach of this technology, because it has been proven to be able to bring a number of value and benefit to the national development significant Indonesia and civilization of mankind in this world. With the advancement in the field of ICT is growing at an exponentially and take the positives out of the field of ICT is expected to be Indonesian nation to excel in all areas.